The Effect of CAR, FDR, NPF and BOPO to Return on Equity - Aprilia, Rani; Witono, Banu (Universitas Pamulang, 2022)
The purpose of this paper is to determine the effect of the capital adequacy ratio, financing to deposit ratio, non-performing financing and operational income operating costs on return on equity at Islamic Commercial Banks in Indonesia for the period 2011 - 2020. This type of research is quantitative, research using secondary data in the form of an annual report. This study uses a sample of 5 Islamic Commercial Banks in Indonesia for the period 2011 - 2020 with the determination of the sample using the purposive sampling method. The technique for analyzing the data in this study uses multiple linear regression, classical assumption test, and hypothesis testing with data processing using the SPSS v.20 application. Based on the results of multiple linear regression analysis, it is obtained that the capital adequacy ratio, non-performing financing and operating costs of operating income have a negative and significant effect on return on equity, while the financing to deposit ratio has no significant effect on return on equity.